2020
DOI: 10.1186/s13287-019-1471-y
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of fatty acid oxidation by increased CPT1A on replicative senescence of placenta-derived mesenchymal stem cells

Abstract: BackgroundHuman placenta-derived mesenchymal stem cells (PD-MSCs) are powerful sources for cell therapy in regenerative medicine. However, a limited lifespan by senescence through mechanisms that are well unknown is the greatest obstacle. In the present study, we first demonstrated the characterization of replicative senescent PD-MSCs and their possible mitochondrial functional alterations.MethodsHuman PD-MSCs were cultured to senescent cells for a long period of time. The cells of before passage number 8 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 310 publications
(201 citation statements)
references
References 38 publications
7
194
0
Order By: Relevance
“…1h). Previously, we confirmed in naïve MSCs as multi-differentiation potentials [19]. After differentiations, osteogenic-specific markers (Osteocalcin; OC and Collagen Type 1 alpha 1; COL1A1) and adipogenic-specific markers (Adipsin and peroxisome proliferator-activated receptor gamma; PPAR-γ) were expressed at high level in differentiated PD-MSCs PRL−1 by qRT-PCR (Fig.…”
Section: Characterization Of Pd-mscs Modified With Prl-1 Genesupporting
confidence: 54%
“…1h). Previously, we confirmed in naïve MSCs as multi-differentiation potentials [19]. After differentiations, osteogenic-specific markers (Osteocalcin; OC and Collagen Type 1 alpha 1; COL1A1) and adipogenic-specific markers (Adipsin and peroxisome proliferator-activated receptor gamma; PPAR-γ) were expressed at high level in differentiated PD-MSCs PRL−1 by qRT-PCR (Fig.…”
Section: Characterization Of Pd-mscs Modified With Prl-1 Genesupporting
confidence: 54%
“…Hepatic lipid metabolism is a complex process involving molecular events involving the roles of transcription factors, lipogenic, and fatty acid transporter genes [ 44 , 45 , 46 , 47 ]. Their modulation can lead to the development of steatosis along with reduced mitochondrial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Seok et al found that CPT1 expression and fatty acid oxidation were increased in senescent human placenta-derived mesenchymal stem cells as compared to their proliferating counterparts, likely through the inactivation of ACC1 [ 78 ]. They also showed that mitochondrial dysfunction, the levels of reactive oxygen species, and senescence were reduced when CPT1 was inhibited [ 78 ], suggesting that CPT1 activity and fatty acid breakdown might play roles in maintaining mitochondrial function in senescence. Overall, these studies suggest the involvement of fatty acid and their metabolism in cellular senescence occur through a complex mechanism that seems to be dependent on tissue type and developmental stage.…”
Section: Various Lipid Classes Have Been Linked To Senescencementioning
confidence: 99%